PALLIATIVE CARE IN GERIATRICS: CURRENT ISSUES AND PROSPECTS - I. P. Рonomareva; K. I. Рrashchayeu (Архивъ внутренней медицины)
The purpose of the study is to identify the main problems and prospects of development of palliative care in geriatrics at the present stage. Method of research was to analyze the printed and electronic databases that meet the stated issues. The results of the study highlight the problems of the development of palliative care in geriatric practice: the lack of a developed procedure of rendering palliative care and adequate elderly patient selection criteria, the lack of trained professional staff. The main prospects-association of palliative practices and concepts of modern geriatrics required specialized geriatric assessment and the provision of clinical, medical, social and socio-psychological geriatric syndromes. While promising option for the development of palliative care geriatrics is the integration into the existing health care system, acceptance of the fact that it is a part of the specialized geriatric care. This requires the involvement and training of not only specialists with medical education, but also persons without medical training from among social workers and volunteers working in palliative care. Therefore, the obtained data allowed to conclude that topical is the development of palliative care in geriatrics, taking into account not only clinical but medico-social, socio-psychological features.